Design, synthesis, conformational analysis, and biological activity of Cα1-to-Cα6 1,4- and 4,1-disubstituted 1H-[1,2,3]triazol-1-yl-bridged oxytocin analogues - Francesca Nuti; Maud Larregola; Agnieszka Staśkiewicz; Bernhard Retzl; Nataša Tomašević; Lorenzo Macchia; Maria E. Street; Michał Jewgiński; Olivier Lequin; Rafal Latajka; Paolo Rovero; Christian W. Gruber; et al. (Taylor & Francis Group, 2023)
Oxytocin (OT) is a neurohypophyseal peptide hormone containing a disulphide-bridged pseudocyclic conformation. The biomedical use of OT peptides is limited amongst others by disadvantageous pharmacokinetic parameters. To increase the stability of OT by replacing the disulphide bridge with the stable and more rigid [1,2,3]triazol-1-yl moiety, we employed the Cu2+-catalysed side chain-to-side chain azide-alkyne 1,3-cycloaddition. Here we report the design, synthesis, conformational analysis, and in vitro pharmacological activity of a homologous series of Cα1-to-Cα6 side chain-to-side chain [1,2,3]triazol-1-yl-containing OT analogues differing in the length of the bridge, location, and orientation of the linking moiety. Exploiting this macrocyclisation approach, it was possible to generate a systematic series of compounds providing interesting insight into the structure-conformation-function relationship of OT. Most analogues were able to adopt similar conformation to endogenous OT in water, namely, a type I β-turn. This approach may in the future generate stabilised pharmacological peptide tools to advance understanding of OT physiology.